Legal Environmental Management Method - Burlani, Rafael; Selig, Paulo Maurício (Revista Gestão da Produção Operações e Sistemas, 2008)
The objective of this study is to introduce a method for legal environmental management aimed at identifying environmental laws during implementation of an environmental management system. In order to achieve this, the method was applied at a thermoelectric venture when it was conducting a study of environmental aspects and impacts for later implementation of the environemntal management system based on ISO 14001. For implementing the optional ISO 14001 norm, it is explicit in imposing the organizatons duty to identify, satisfy and evidence compliance with environmental legislation. There is also pressure from environmental entities, Brazilian courts and society that demand organizations have an appropriate relationship in terms of their activities and the maintenance, prevention and defense of the environment. This study developed a legal environmental management method aimed at helping organizations that seek ISO 14001 certification, and as a consequence agree with the limits and parameters instituted by environmental legislation. Key words: Environmental Management; Method; Environmental Legislation